2020
DOI: 10.1177/1046878119899424
|View full text |Cite
|
Sign up to set email alerts
|

A Framework of Simulation and Gaming for Enhancing Community Resilience Against Large-Scale Earthquakes: Application for Achievements in Japan

Abstract: Background. The significance of mutual-help in communities for disaster management is a fundamental important concept. However, the current societal state does not reflect this lesson. S&G (Simulation and Gaming) has the potential to overcome the challenges faced in promoting community-based disaster management. No scientific research is currently present that reviews their achievements in Japan. Aim. This paper analyzes the current achievements of S&G in enhancing community resilience against large-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Research conducted in Japan using the S&G (Simulation and Gaming) method resulted in an increase in community resilience to large-scale earthquakes in Japan with a significant value of resilience increasing in the event of an earthquake (Toyoda, 2020). Research conducted in Iran using lecture, question and answer and group discussion methods, showed that the knowledge in the intervention group increased compared to the control group with p<0.001 (Amini et al, 2021).…”
Section: Program Evaluation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted in Japan using the S&G (Simulation and Gaming) method resulted in an increase in community resilience to large-scale earthquakes in Japan with a significant value of resilience increasing in the event of an earthquake (Toyoda, 2020). Research conducted in Iran using lecture, question and answer and group discussion methods, showed that the knowledge in the intervention group increased compared to the control group with p<0.001 (Amini et al, 2021).…”
Section: Program Evaluation Resultsmentioning
confidence: 99%
“…Securing furniture, providing food and water, finding designated evacuation centers, preparing emergency equipment, discussing disaster planning with family members, seeking help from neighborhood residents and vice versa in times of disaster (Arulmohi et al, 2017). Knowledge of best indoor evacuation or self-rescue practices and self-efficacy in the face of earthquake emergencies to anticipate and mitigate impacts, restoring people's lives by quickly managing shelters (Feng et al, 2020;Gampell et al, 2021;Toyoda, 2020). Places that can be used to protect themselves in the event of an indoor earthquake, how to manage anxiety in the event of an earthquake and (3) First aid in the event of an earthquake with steps to avoid physical injury by avoiding dangerous items that are passed by when escaping if an earthquake occurs (Li et al, 2017).…”
Section: Program Materialsmentioning
confidence: 99%
“…Following Bekebrede (2010) and Toyoda (2020), a gaming session consists of 1) a briefing, 2) game play, and 3) a debriefing -with some possible feedback loops and iterative steps in between. In addition to this, a debriefing can be described as a micromacro-cycle model (Kern, 2003) in which a simulation game is understood as one intervention next to other possibilities.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Shifting community resilience to an analytical level, Toyoda (2020) demonstrated that resilience can be viewed from three perspectives: stability (absorption), recovery (bouncing back), and transformation (adaptability). Recovery rarely occurs in the direction of a preexisting state, therefore, necessitating some consideration for regaining life functions as exhibited by one's experiences in evacuation shelters.…”
Section: General Characteristics Of Community Resiliencementioning
confidence: 99%